Keabsahan Nikah Syigar Dan Mahar Mitsil Persepektif Imam Abu Hanifah - Darlius, Darlius (STAIN MAJENE, 2024)
This research is related to the thoughts of Imam Abu Hanifah who allows shigar marriages on the condition that both men must pay the mitsil dowry. This research seeks to reveal the reasons and legal guidelines used by Abu Hanifah regarding the permissibility of shigar marriage. This research method is library research which examines literature related to the research discussion, namely the books of al-Mabsuth and Badi'us Sana'i. Data were analyzed using descriptive analysis methods. Abu Hanifah is of the opinion that syighar marriage is prohibited because it makes the honor (budu') of the two women being married as a dowry, even though a woman's honor should not be used as a dowry, so that the dowry from the marriage becomes damaged (fasid), whereas